(untitled) (Window of Public Health Journal, 2025)
The working environment conditions that trigger excessive heat production in the worker’s body are referred to as heat stress. Factors that influence it include air temperature, humidity levels, wind movement, and radiation temperature. As a result of this heat stress, the body undergoes a complex physiological response, collectively referred to as heat strain. This study aims to determine the relationship between heat stress exposure and the risk of heat strain in port area workers at PT. Multi Surindo, Makassar City. This study used a quantitative research method with a cross-sectional approach. The sampling technique employed in this study was total sampling, with a sample size of 60 respondents. The results showed a relationship between heat stress and the risk of heat strain (p = 0.028), there was a relationship between drinking water consumption and the occurrence of heat strain (p = 0.002), there was a relationship between workload and the risk of heat strain (p = 0.028), and there was a relationship between work duration and the risk of heat strain (p = 0.000). Conversely, there was no relationship between medical history and the risk of heat strain (p = 0.884). This study concludes that understanding these relationships can inform targeted interventions aimed at reducing the risk of heat strain among port workers. The researchers’ suggestions are the importance of monitoring their physical condition when exposed to excessive heat in the work environment and companies are advised to provide sufficient drinking water for workers in areas exposed to heat to prevent dehydration.